A Bit of Old China - Stoddard, Charles Warren, 1843-1909 (Salt Lake City, UT : Project Gutenberg, 2002)
"A Bit of Old China" by Charles Warren Stoddard is a vivid account of the Chinese Quarter in San Francisco, presented as a travel narrative written during the late 19th century. The book navigates the bustling streets of Chinatown, offering observations on the life, culture, and vibrant community of Chinese immigrants amidst an American backdrop. It explores themes of identity, cultural contrasts, and the struggles within the immigrant experience. In this richly descriptive work, Stoddard immerses readers in the sights, sounds, and scents of Chinatown, illuminating the lives of its inhabitants, from prosperous merchants to the impoverished coolies. The author captures the complexity of the community, touching on aspects such as commerce, labor, gambling, and opium use while also reflecting on the grandeur and squalor that coexist in this unique cultural enclave. As readers journey through the streets and underground tenements, they witness the stark realities of life for many immigrants, alongside the remnants of their cultural practices, such as rituals at the Joss House. The narrative ultimately encapsulates the essence of Chinatown as a microcosm of broader societal themes, reflecting both the struggles and the contributions of the Chinese community in America. (This is an automatically generated summary.)
Release date is 2002-07-01
Produced by David A. Schwan, and David Widger
Keywords: Chinese -- California -- San Francisco